Research on the Collaborative Development of Marine Awareness Education Between Local Colleges and Primary and Secondary Schools Under the Symbiotic Theory - CHEN Anqi; XU Hongyu; QIU Fengyan; ZENG Jingyi; GU Mindong; HUANG Aiping (Haiyang Kaifa yu guanli)
Marine awareness education plays an important role in promoting the construction of a marine power, but the current status of national marine awareness still cannot match the booming marine practice in China, so it is urgent to improve and perfect the marine awareness education system in the whole education stage. Based on this, on the basis of grasping the research progress of marine awareness education at home and abroad, this paper conducts a survey on universities and primary and secondary schools in Zhanjiang City, analyzes the necessity of the collaborative development of marine awareness education between local universities and primary and secondary schools, and explores the realization path of the collaborative development of marine awareness education between local universities and primary and secondary schools under the framework of symbiosis theory. It is found that the collaborative development of marine awareness education under the symbiotic theory has the advantages of promoting resource sharing, making up for the shortcomings of both sides, paying attention to sustainable development, and coordinating and complementing each other. Therefore, in order to realize the cooperative development of marine awareness education between local colleges and primary and secondary schools in the three levels of symbiotic unit, symbiotic mode and symbiotic environment, we should build cooperative participation channels and exert the joint force of symbiotic unit. To innovate the form of marine awareness education and build a model of collaborative integration; Establish a collaborative development concept of marine awareness education and optimize the symbiotic environment.